Evaluation of cardiac modulation in children in response to apnea/hypopnea using the Phone Oximeter™. (5th January 2016) - Dehkordi, Parastoo; Garde, Ainara; Karlen, Walter; Petersen, Christian L; Wensley, David; Dumont, Guy A; Mark Ansermino, J
Abstract: Individuals with sleep disordered breathing (SDB) can experience changes in automatic cardiac regulation as a result of frequent sleep fragmentation and disturbance in normal respiration and oxygenation that accompany most apnea/hypopnea events. In adults, these changes are reflected in enhanced sympathetic and reduced parasympathetic activity. In this study, we examined the autonomic cardiac regulation in children with and without SDB, through spectral and detrended fluctuation analysis (DFA) of pulse rate variability (PRV). PRV was measured from pulse-to-pulse intervals (PPIs) of the photoplethysmogram (PPG) recorded from 160 children using the Phone Oximeter ™ in the standard setting of overnight polysomnography. Spectral analysis of PRV showed the cardiac parasympathetic index (high frequency, HF) was lower ( p < 0.01) and cardiac sympathetic indices (low frequency, LF and LF/HF ratio) were higher ( p < 0.01) during apnea/hypopnea events for more than 95% of children with SDB. DFA showed the short- and long-range fluctuations of heart rate were more strongly correlated in children with SDB compared to children without SDB. These findings confirm that the analysis of the PPG recorded using the Phone Oximeter ™ could be the basis for a new screening tool for assessing PRV in non-clinical environment.